The Use of Comparative and Repetitive Language Styles in the Collection of Geguritan Sêrat Plérok by Yusuf Susilo Hartono - Kirana, Yolanda Nira; Waluyo, Budi; Fitriana, Tya Resta (Universitas Sebelas Maret, 2024)
This study describes the comparative style of language found in the collection of Sêrat Plérok geguritan by Yusuf Susilo Hartono. The purpose of this study is to determine the form of comparative language style in the geguritan group of Sêrat Plérok. The research method used is a qualitative descriptive method with a stylistic approach. The data collection technique used in this research is document analysis. The source of the data used in this research is the anthology book geguritan Sêrat Plérok by Yusuf Susilo Hartono. The data used is geguritan which contains comparative language styles, the number of data found is 11 data. The results of this study are (1) simile style with 2 data, (2) metaphor language style with 4 data, and (3) personification style with 5 data. The conclusion in this study, the author wrote three comparative language styles from four types of comparative language styles in eleven data to compare things and beautify vocabulary. Comparative language style that is not found in the geguritan Sêrat Plérok anthology is allegorical style.